Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18179303
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Work Engagement in the Association between Psychological Capital and Safety Citizenship Behavior in Coal Miners: A Mediation Analysis

Abstract: With the development of science and technology and the increasing importance attached by to these domains by the state and government departments in recent years, China’s coal production and safety supervision level continue to increase. However, the prevalence of frequent coal mine safety accidents has not been effectively curbed. The main purpose of this study was to explore the mediating role of work engagement in the relationship between psychological capital and safety citizenship behavior among Chinese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Work engagement played an intermediary role in the influence of owners’ safety management behavior on construction workers’ SCB. Work engagement also played a mediating role in many studies on proactive behavior, e.g., [ 20 , 28 ]. The results of this study confirmed the mediating role of work engagement in Wilmar’s extended JD-R model [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work engagement played an intermediary role in the influence of owners’ safety management behavior on construction workers’ SCB. Work engagement also played a mediating role in many studies on proactive behavior, e.g., [ 20 , 28 ]. The results of this study confirmed the mediating role of work engagement in Wilmar’s extended JD-R model [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that individual characteristics and psychological and organizational factors have an impact on the SCB of construction workers [ 18 ]. Previous studies on SCB mostly considered employee personality and psychological factors [ 19 , 20 ]. One study conducted research from an organizational perspective, including the organization’s safety atmosphere and level of support [ 21 ], while other studies considered the impact of leadership [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that higher levels of occupational stress and burnout were associated with increased detection of positive psychological symptoms in coal miners. Poor mental health status is associated with the unsafe behaviors of coal miners and has a predictive effect on the occurrence of coal mine accidents ( 50 ). Consequently, this study provides the data support and intervention direction for coal mine management enterprises to pay attention to the psychological health of coal miners, which is also significant in improving the occupational life quality of coal miners and ensuring the safety production of coal mining enterprises.…”
Section: Discussionmentioning
confidence: 99%